2019
DOI: 10.1016/j.phrs.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Gut-derived serotonin contributes to bone deficits in colitis

Abstract: Osteoporosis and bone fractures occur at higher frequency in patients with inflammatory bowel disease (IBD), and decreased bone mass is observed in animal models of colitis. Another consistent feature of colitis is increased serotonin (5-HT) availability in the intestinal mucosa. Since gut-derived 5-HT can decrease bone mass, via activation of 5-HT receptors on pre-osteoblasts, we tested the hypothesis that 5-HT contributes to bone loss in colitis. Colitis was chronically induced in mice by adding dextran sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Conversely, inhibition of gutderived serotonin might become a treatment option for osteoporosis. These findings are now experimentally observed in animal studies, and corroboration of these findings in humans is awaited [45,46].…”
Section: Introductionmentioning
confidence: 56%
“…Conversely, inhibition of gutderived serotonin might become a treatment option for osteoporosis. These findings are now experimentally observed in animal studies, and corroboration of these findings in humans is awaited [45,46].…”
Section: Introductionmentioning
confidence: 56%
“…25 To date, only 1 study has reported a potential link between high GDS levels and bone deficits in DSS model of colitis. 26 However in this study, authors reported GDS-mediated effects on bone pathology only for 21 days of colitis. Unlike studies in models of chemically induced colitis, Winnie mouse model permits bone studies for the long-term, throughout the chronic disease course for up to approximately 6 to 7 months, thus, mimicking the onset and progression of UC.…”
Section: Introductionmentioning
confidence: 60%
“…This alteration in bone microarchitecture is in agreement with earlier reports in a model of DSS-induced colitis. 11,26 Biomechanical studies have demonstrated that the structural properties of whole-bone specimens are highly determined by the contribution of cortical bone. 47 To understand the quality and strength of cortical bone compartments, we subjected bones from Winnies and controls to a 3-point bending test to determine ultimate force (the maximum force that breaks the bone).…”
Section: Discussionmentioning
confidence: 99%
“…24 To date, only one study has reported a potential link between high GDS levels and bone deficits in DSS model. 25 However, in this study GDS-mediated effects on bone pathology have been revealed for 21 days of colitis only. Interestingly, a high level of GDS is prominent in Winnie mice.…”
Section: Mouse Models Have Been Widely Used To Understand Pathophysiomentioning
confidence: 74%
“…Consistently, Lavoie et al (2019) demonstrated deleterious effect on bone caused by high GDS levels in the DSS model of colitis. 25 It has been speculated that GDS triggers immune cells for the production of proinflammatory mediators in the context of intestinal inflammation and inflammatory joint diseases. 24,38 Likewise, GDS may have a pro-inflammatory role in causing bone loss in colitis.…”
Section: Discussionmentioning
confidence: 99%